A new Li-based ceramic of Li4MgSn2O7: Synthesis, phase evolution and microwave dielectric properties. Issue 16 (December 2018) - Zuo, Ruzhong; Qi, He; Qin, Fang; Dai, Qianlong
Abstract: A pure-phase Li4 MgSn2 O7 (L4 MS) was successfully synthesized through optimizing the calcination condition. Microwave dielectric properties of the L4 MS ceramic with the phase evolution were investigated together with its low-temperature sintering. The sample maintains a single L4 MS phase as sintered below 1200 °C, such that τf remains a constant value of ∼12.4 ppm/°C. Accompanied by the appearance of impurity phases (Li2 SnO3 )ss and especially (MgO)ss at higher sintering temperatures, excellent microwave dielectric properties of εr  = 13.1–13.5, Q × f = 106, 800–126, 810 GHz and τf  = 0–−4.2 ppm/°C are obtained in samples sintered at 1215–1260 °C for 4 h. Reduction of sintering temperature using LiF sintering aid also helps achieve pure-phase dense L4 MS ceramic. The L4 MS + x wt.% LiF ceramic exhibits εr ∼13.7, Qxf∼97, 000 GHz (x ≤ 3) and τf ∼8–13 ppm/°C sintered at 850 °C for potential LTCC applications, and εr ∼13.9, Qxf∼146, 000 GHz and τf ∼1.5–6 ppm/°C (x ≥ 4) as sintered 1000 °C, exhibiting large potentials for microwave dielectric candidates.